Surgical Management of Solitary Thyroid Nodule - Shaif, Burkan Nasr Rashed (Current Practice in Medical Science Vol. 11, 2022)
Preoperative differentiation between benign and malignant in solitary thyroid nodules is crucial due to the rising incidence of thyroid cancer in these lesions. Additionally, it aids in preventing unnecessary surgery and its side effects, such as hypothyroidism, hypocalcemia, and repeated nerve damage. In this study ,135 cases of clinically detected solitary thyroid nodules,126 female and 9 male patients, between 14_65 years age, median 41 years and mean 39.76 years, (94, 41)patients respectively Right side thyroid effect more than Left side, Fine needle aspiration cytology (FNAC) sensitivity, specificity and accuracy was (61% , 72% , 64%)respectively. Postoperative histopathology reported 100 (74%) patients as having benign thyroid nodules and 35 patients (26%) as having malignant thyroid nodules. 9 patients (7%) experienced postoperative transitory hypocalcemia, while 3 patients (2%) experienced transient hoarseness. The incidence of malignancy in solitary thyroid nodules is high and depends on preoperative evaluation, including history, examination, ultrasound, Fine needle aspiration cytology (FNAC) result, and intraoperative assessment of the nodule. Malignant nodules frequently exhibit rapid growth by history, a hard-fixed nodule on physical examination, hypoechoic, micro-calcification, and cervical lymphadenopathy on thyroid ultrasound. Age, the number of nodules, and the size of the nodules are not mentioned as risk factors for thyroid cancer in men. If performed with ultrasound guidance and analysed by histopathologists with experience, fine needle aspiration cytology (FNAC) is more beneficial for diagnosis. When performed by skilled surgeons, thyroid surgery has fewer difficulties.